Biomicroscopic Lenses to Visualise Posterior Segment - Khushboo Chawla; Shraddha Raj Shrivastava (Delhi Journal of Ophthalmology)
Ophthalmology is a unique field allowing the clinician a non-invasive ‘window’ to the organ of interest as the eye and especially its posterior segment hide's information, not just about eye-related issues but also about the patient's general well-being. Although newer technologies like Optical Coherence Tomography (OCT) and other retinal imaging modalities have revolutionised the diagnosis and management of posterior segment pathologies, they are still not a replacement for the easily available, affordable and portable hand-held lenses. By utilising the optics of these lenses, we are able to visualise the remote areas of the eye especially the fundus, in order to facilitate any therapeutic interventions. This article focuses on the various types of lenses used for posterior segment evaluation which are important tools in every ophthalmologists' arsenal.